A new prozostrodontian cynodont (Therapsida) from the Late Triassic Riograndia Assemblage Zone (Santa Maria Supersequence) of Southern Brazil - SOARES,MARINA B. (2014)
We report here on a new prozostrodontian cynodont, Botucaraitherium belarminoigen. et sp. nov., from the Late Triassic RiograndiaAssemblage Zone (AZ) of the Candelária Sequence (Santa Maria Supersequence), collected in the Botucaraí Hill Site, Candelária Municipality, state of Rio Grande do Sul, Brazil. The new taxon is based on a single specimen (holotype MMACR-PV-003-T) which includes the left lower jaw, without postdentary bones, bearing the root of the last incisor, canine and four postcanines plus one partial crown inside the dentary, not erupted, and two maxillary fragments, one with a broken canine and another with one postcanine. The features of the lower jaw and lower/upper postcanines resemble those of the prozostrodontians Prozostrodon brasiliensis from the older HyperodapedonAZ and Brasilodon quadrangularis and Brasilitherium riograndensisfrom the same RiograndiaAZ. The inclusion of Botucaraitheriumwithin a broad phylogenetic analysis, positioned it as a more derived taxon than tritylodontids, being the sister-taxon of Brasilodon, Brasilitheriumplus Mammaliaformes. Although the new taxon is based on few cranial elements, it represents a additional faunal component of the Triassic RiograndiaAZ of southern Brazil, in which small-sized derived non-mammaliaform cynodonts, closely related to the origin of mammaliaforms, were ecologically well succeed and taxonomically diverse.